Administrative Service System for the Community in Tanjung Kerang Village - Zamrozi, Adi; Sanmarino, A (Jurnal Sistem Informasi dan Teknik Informatika (JAFOTIK), 2023)
In this study, the challenges faced by Tanjung Kerang Village in providing optimal community administration services using conventional methods are highlighted. The village, despite having a relatively large population, faces issues such as long queues, delays due to forgotten requirements, and difficulties in accessing data for administrative processes. To address these challenges, the study proposes the implementation of a community service administration information system using the Prototype Model in software development. The Prototype Model, characterized by quick iterations, user involvement, and continuous refinement, is chosen as the methodology for system development. This approach allows for the creation of a preliminary version of the software that undergoes testing and refinement in multiple cycles. The iterative nature of the model, coupled with user feedback, facilitates the gradual convergence towards a final, fully functional system. In conclusion, the Prototype Model proves instrumental in addressing the identified challenges, offering a systematic and iterative approach to enhance community administration services. The proposed information system has the potential to significantly improve service delivery, making it more effective and efficient for both administrators and the community.